PENGARUH INTERAKTIF ANTARA FAKTOR INDIVIDUAL DAN KONDISI INSTITUSIONAL TERHADAP ENTREPRENEURIAL ENGAGEMENT - Riana Susanti; Askardiya Radmoyo Adji (Jurnal Pengembangan Wiraswasta, 2019)
The purpose of this study is to investigate the direct influence of individual factors including individuals’ income and individual education levels on entrepreneurial engagement, as well as the influence of institutional conditions, including government policy and universities supports on the relationship between individual factors and individuals’ entrepreneurial engagement. Cross sectional study was used to test the research hypotheses. The data was collected through questionnaires which were distributed to Members of Indonesian Chamber of Commerce and Industry in Jakarta where the industries and investment activities are centralized. A random sample of 345 members was used to collect the data. The response rate was 91%. The results show a significant positive direct effect of individual factors on the entrepreneurial engagement. Institutional conditions, including government policy and universities supports, have a positive effect on the relationship between individual factors and entrepreneurial engagement. This research is useful for prospective entrepreneurs in Indonesia so that they can utilize the resources they have in the entrepreneurial engagement process. Likewise it will help the institutional parties that influence the process of entrepreneurial engagement in creating entrepreneurial atmosphere and culture. Keywords: Individual Factors, Institutional Conditions, Entrepreneurial Engagement, Entrepreneurship in Indonesia Tujuan dari penelitian ini yaitu untuk menyelidiki pengaruh langsung faktor individual, meliputi tingkat pendapatan dan pendidikan individu terhadap entrepreneurial engagement, termasuk pengaruh kondisi institusional, meliputi kebijakan pemerintah dan dukungan universitas, terhadap hubungan antara faktor individual dan entrepreneurial engagement. Studi cross sectional digunakan untuk menguji hipotesis. Data dikumpulkan melalui kuesioner yang didistribusikan kepada anggota Kadin Jakarta dimana kegiatan industri dan investasi terpusat. Sampel acak sebanyak 345 anggota digunakan untuk mengumpulkan data. Tingkat respon sebanyak 91%. Hasil menunjukkan pengaruh langsung faktor individual signifikan positif terhadap entrepreneurial engagement. Kondisi institusional, meliputi kebijakan pemerintah dan dukungan universitas berpengaruh positif dalam hubungan antara faktor individual dan entrepreneurial engagement. Penelitian ini berguna untuk calon wirausaha di Indonesia sehingga mereka dapat memanfaatkan sumber daya yang dimiliki dalam proses entrepreneurial engagement. Begitu juga akan membantu pihak insitusional yang mempengaruhi proses entrepreneurial engagement dalam penciptaan suasana dan budaya kewirausahaan. Kata Kunci: Faktor Individual, Kondisi Institusional, Entrepreneurial Engagement, Kewirausahaan di Indonesia